The role and impact of modern internet tools in the management of the company - Jacek, Paulina (Funkcjonowanie e-biznesu. Zasoby, procesy, technologie, 2015)
Currently, each person has a computer, tablet or phone. We are dependent on access to the Internet. All the time we need to get information, the Internet facilitates us. Every step, we use Internet tools at work or at home. In this article, I would like to present the topic just related to online tools. Firstly I’ll start from the need for a computer in the modern world. Then I explain what it the Internet and why we use it. Another part will deal with results research conducted the research team SKN ProBiz+ on entrepreneurship students of the University of Lodz. The last past will summarize my conclusions collected.